2005
DOI: 10.1177/107424840501000203
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk of Selective Cyclooxygenase-2 Inhibitors

Abstract: Recently, cyclooxygenase-2 (COX-2) inhibitors (coxibs), a class of drugs intended to be painkillers, have created unprecedented controversy because of their cardiovascular risk profile. The controversy has affected the patients, health-care providers, the Food and Drug Administration, and the manufacturers of these agents alike. We summarize the mechanisms of actions of this class of agents, their cardiovascular risk as evident in multiple trials, the basis of their adverse risk profile, and our views on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although studies have suggested that COX-2 inhibition may be beneficial in cancer prevention, recent data raise concern regarding cardiovascular toxicities associated with the use of COX-2 inhibition (Schrör et al, 2005). An alternative approach that could potentially avoid this toxicity includes targeting other elements in the prostanoid pathway downstream of COX-2.…”
mentioning
confidence: 99%
“…Although studies have suggested that COX-2 inhibition may be beneficial in cancer prevention, recent data raise concern regarding cardiovascular toxicities associated with the use of COX-2 inhibition (Schrör et al, 2005). An alternative approach that could potentially avoid this toxicity includes targeting other elements in the prostanoid pathway downstream of COX-2.…”
mentioning
confidence: 99%
“…An incomplete and simplistic interpretation of the processes and mechanisms that regulate these important enzymes may have led to the initial poor understanding of the adverse events, followed by warnings and withdrawals, a lop-sided sequence in drug approval. The mechanism of action of the cyclooxygenases (COX) was first described by Vane (1971) and is summarized in Figure 1 [ Schrör et al 2005].…”
Section: Physiology Of the Cox Enzymesmentioning
confidence: 99%
“…Arachidonic acid metabolism via cyclooxygenase-1 and cyclooxygenase-2 in the cardiovascular system. Potential mechanisms for COX-2 inhibition related thrombosis and hypertension [Schrör et al 2005].…”
Section: Figurementioning
confidence: 99%